BESAR RISIKO KEJADIAN INFEKSI TB ANAK SD MENURUT KONTAK PENDERITA TB DAN KARAKTERISTIK ORANG TUA DI KABUPATEN JEMBER - Prasetyowati, Irma (FKM - UNEJ, 2008)
With the detection of tuberculosis (TB) infection in children means that there are transmitting infection by the lung TB carrier with positive AFB sputum. The transmission more frequently occurred in one roof close contact. The objective of this study is to know the odds ratio of TB infection in primary school student according to TB patient contact and parents characteristics. This study was perfomed from January to Juny 2008 using case control study design. The cases group consisting of 17 children were TB infected and the control group consisting of 51 children werenât TB infected. The analysis showed that children who had contact with TB patient were 56.25 times (95% CI with OR 6.254-505.962), who had contact chronic coughs patient were 14.22 times (95% CI with OR 3.155-64.112,) who had mother work were 6.5 times (95%CI 1.838-22.981) and who had low parents earning were 7.8 times (95%CI 2.285-26.622) more likely to have TB infected. Considering that contact TB patient and parents characteristics are risk factors for TB unfection. Early Â diagnosis prompt treatment for contact, and working mother must give deeper attention takes care of child TB infection. Keywords: Tuberculosis, TB patient contact, parents characteristic, odds ratio